2019
DOI: 10.24059/olj.v23i2.1449
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Developing Videos for Online Learning: A Seven-Principle Model

Abstract: Despite the ubiquitous use of instructional videos in both formal and informal learning settings, questions remain largely unanswered on how to design and develop video lessons that are often used as the primary method for delivering instruction in online courses. In this study, we experimented with a model of seven principles drawn from instructional design theories for designing and developing video lessons for an online graduate course. Feedback was collected from students through surveys on their perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 36 publications
4
79
1
11
Order By: Relevance
“…All students from both universities agreed that videos that lack any vocal explanation are not effective. In support of this view, Ou, Joyner, & Goel (2019) noted educational video, which displays instructor's writing along with their voiceover, recreates natural features of an in-person classroom.…”
Section: Resultsmentioning
confidence: 86%
“…All students from both universities agreed that videos that lack any vocal explanation are not effective. In support of this view, Ou, Joyner, & Goel (2019) noted educational video, which displays instructor's writing along with their voiceover, recreates natural features of an in-person classroom.…”
Section: Resultsmentioning
confidence: 86%
“…Interactive online learning activity with personalizable options enable learners to be more focused and engaged as they can select the learning level that matches their skills (Pandey, 2017). Ou, Joyner, and Goel (2019) also emphasized the critical role of personalized online teaching materials in stimulating learners' interest and engaging them in learning.…”
Section: The Role Of An Interactive Visual Learning Tool and Its Persmentioning
confidence: 99%
“…These activities referred as ADDIE and labelled as basic ID Model [24]. As a finding on their previous study, Ou, Joyner & David [21] emphasized that video lessons are vital to the success of an online course. The study about students' insights on the use of video lectures in an online class found that students' satisfaction with the course videos had a strong relationship with a positive overall learning experience [22].…”
Section: E) Standardize Criteria Of Video Lecturesmentioning
confidence: 89%
“…As for online learning, physically present as FtF lecturing should be mediated by both video lectures (asynchronous) or video conferencing (synchronous). The finding is that video lessons are vital to the success of an online course [21]. The study about students' insights on the use of video lectures in an online class found that students' satisfaction with the course videos had a strong relationship with a positive overall learning experience [22].…”
Section: D) Process Of Creating Online Course Modulementioning
confidence: 99%